Phenylpropanoid Scent Compounds in Petunia x hybrida Are Glycosylated and Accumulate in Vacuoles - Cna'ani, Alon; Shavit, Reut; Ravid, Jasmin; Aravena-Calvo, Javiera; Skaliter, Oded; Masci, Tania; Vainstein, Alexander (Frontiers in Plant Science, 2017)
Floral scent has been studied extensively in the model plant Petunia. However, little is known about the intracellular fate of scent compounds. Here, we characterize the glycosylation of phenylpropanoid scent compounds in Petunia x hybrida. This modification reduces scent compounds' volatility, reactivity, and autotoxicity while increasing their water-solubility. Gas chromatography–mass spectrometry (GC–MS) analyses revealed that flowers of petunia cultivars accumulate substantial amounts of glycosylated scent compounds and that their increasing level parallels flower development. In contrast to the pool of accumulated aglycones, which drops considerably at the beginning of the light period, the collective pool of glycosides starts to increase at that time and does not decrease thereafter. The glycoside pool is dynamic and is generated or catabolized during peak scent emission, as inferred from phenylalanine isotope-feeding experiments. Using several approaches, we show that phenylpropanoid scent compounds are stored as glycosides in the vacuoles of petal cells: ectopic expression of Aspergillus niger β-glucosidase-1 targeted to the vacuole resulted in decreased glycoside accumulation; GC–MS analysis of intact vacuoles isolated from petal protoplasts revealed the presence of glycosylated scent compounds. Accumulation of glycosides in the vacuoles seems to be a common mechanism for phenylpropanoid metabolites.